Dımaşk'ın En Zor Yılı: Şehrin Moğollar Tarafından İşgali (658/1260) - (:unkn) unknown (My University, 2017)
0

Following the invasion of Baghdad in 656 (1258), the Mongols headed further west in Muslim lands. At the time, Ayyubids controlled Bilad al-Sham while Mamluks ruled in Egypt, having put an end to Ayyubid domination ten years earlier. The Mongols' massacres and usurpation, especially when they captured Aleppo, cau- sed great fear and anxiety throughout the region. Therefore, many of the cities in the region, including Damascus, the most important centre of Bilad al-Sham, sur- rendered to the Mongols without any resistance. The Ayyubid dynasty collapsed with the Mongols' invasion of Damascus, a city which remained in Mongol hands for about eight months until they were defeated by the Mamluks in the battle of 'Ain Jalut. The Mongol invasion led to significant changes in religious, scientific and economic life in Damascus, and changed the political and military structures in the city. The invasion of Damascus caused basically three major developments: High tension in Muslim-Christian relations and the attempt to establish a new social order; building relations with scholars ('ulama') through appointments to teaching positions, and the reorganization of positions themselves; and finally the migration of people, including scholars, from the city due to insecure conditions. This article deals with the developments that took place in Damascus during the Mongol invasion and the following restoration period, with a special reference to their influence upon the scholarly community of the city.
The Hardest Year of Damascus: The Invasion of the City by the Mongols (658/1260)
Keywords: Din Bilimi